Pemilikan Hak Atas Tanah Bagi Warga Negara Asing - Rokilah Rokilah; Mia Mukaromah (Universitas Serang Raya, 2018)
This writing aims to find out how land ownership rights for Foreign Citizens as regulated in the Agrarian Basic Law (UPPA) Number 5 of 1960, in the UPPA regulate the prohibition on land ownership for Foreign Citizens. This is to reduce the existence of ownership rights to land for foreigners. Because in addition to keeping the land of Indonesian citizens not controlled by the foreigners also helping Indonesian citizens to be able to use their land to support their lives. Prohibition of land ownership rights for foreign nationals as stipulated in Article 21 of the BAL there are also exceptions to the prohibition, foreigners can use the right to use to build buildings or open a business. The method used is the empirical normative legal research method, namely the incorporation of normative legal provisions (laws) with empirical elements (legal events in society/social elements).